MEDIA LITERACY LEARNING FOR CHILDREN SCHOOL IN BANDUNG - Agus Setiaman; Kismiyati El Karimah; Dadang Sugiana (Proceeding of International Conference on Art, Language, and Culture, 2017)
The presence of media in the midst of human life certainly had an impact on our behavior patterns, either in the form of understanding, mental attitudes, as well as concrete actions. In every use of the media must be contained messages or accompanying information and consciously accepted by its users, which in turn will affect their behavior. This study aims to identify and obtain an overview about media literacy study conducted in the Junior High School. The method used in this research is qualitative method with case study approach. While the theory used in this research is the theory of the Media Literacy by Potter. The results of this study found that basically media literacy is an alternative that aims to empower the public in the middle of the media siege. This concept has the aim to educate the public to be able to interact and use the media intelligently and critically, so that the public does not easily "fooled" and exploited by the media's interests are not aligned on the needs of the public. Meanwhile, the teenager mentally junior high school students are very vulnerable public to easily affected by media content, while seen from the number of media they use the most widely used.